“Apakah kami anak-anak yang memberontak?” Studi fenomenologi makna kemandirian bagi remaja generasi Z - Surahman, Surahman (Jurnal Psikologi Udayana; Vol 9 No 1 (2022)DO - 10.24843/JPU.2022.v09.i01.p09, 2022)
Generation Z adolescents as a group of individuals who know internet technology from an early age have a different autonomy from the previous generations. The autonomy experienced by generation Z adolescents is followed by behavior that is difficult to understand and sometimes misinterpreted as rebellion, for example disagreeing with their parents and doing things without the help of their parents anymore. Based on this phenomenon, this study aims to analyze the meaning of autonomy for generation Z adolescents. This study uses a qualitative approach with phenomenological methods. Data were collected using semi-structured interviews and then analyzed using the Interpretative Phenomenological Analysis (IPA) technique on four adolescents (19-21 years). Based on the results of the analysis obtained the meaning of independence for generation Z adolescents, namely: (1) efforts to reduce intervention / assistance from parents; (2) differing views with parents; (3) accept the opportunity of parents to make decisions; and (4) the initiative to build work experience.